Metals Powders Synthesis and Processing - Gómez Cuevas, Francisco Paula (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book gathers several manuscripts dealing with powder metallurgy processing. Both powders production and their processing to reach a final product can be found. In particular, the extraction of Ta and Ti powders from their oxides by the action of Mg is studied. Moreover, the synthesis of ball-milled Mn-Bi powder for magnetic uses is also presented in the book. Regarding powders processing, sintering of Fe-Co-Cu powder mixtures for their use as diamond impregnated tools, electrical resistance sintering of mechanically alloyed amorphous Al-Ti powders, cold pressed Fe-Si-B alloys with magnetic uses, hot extruded functionally graded Al-based materials, space holder sintering of Ti for medical implants, sintering of hard Co-based material, and electrical resistance sintering of Fe-WC hardmetals can be found in this book.